Academic Dishonesty Among Virtual Radiologic Technology Students During the COVID-19 Pandemic. - Beinschroth, Kristin; Little, Jennifer; Bhavsar, Grishma (Radiologic Science & Education, 2023)
Education became complex for teachers who had to rapidly replace face-to-face radiologic sciences courses with virtual learning during the COVID-19 pandemic. This cross-sectional study sampled 170 radiology students in California using an online survey and investigated academically dishonest behaviors in virtual courses during the pandemic. Students are more likely to engage in academically dishonest behaviors in virtual courses than in face-to-face courses. Digital tracking software, like lockdown browsers, discouraged dishonest behaviors, whereas online access and increased stress/anxiety made students more likely to cheat. The findings of this study inform radiologic science educators of factors that affect students' cheating likelihood.